Information Technology Governance Self-Assessment Application Using Cobit 5 for Supporting Smart Cities - Aisyah Nuraeni; Toto Suharto (Institute of Computer Science (IOCS), 2020)
Information technology governance self–assessment application aims to align the evaluation process that requires a large enough resource both in human resources, cost, and time. By knowing the portrait of information technology governance conditions, a City can control the information technology investment that has been issued so that it is in line with the goals of the City and supports the implementation of a Smart City. The research method used is a qualitative method with COBIT 5 as the Information Technology Governance Evaluation framework. Meanwhile, the software development method used is Rapid Application Development (RAD) with the Unified Modeling Language (UML) design model. The result obtained is a ranking of the maturity level of information technology governance with application media as a means of collecting assessment data so that it can help improve the efficiency of the implementation of Information Technology Governance Evaluation in Cities.